Research and education on racism in Denmark: The state of the field - and where to from here - Midtvåge Diallo, Oda-Kange; Guschke, Bontu Lucie; Hunter, Elizabeth Löwe; Khawaja, Iram; Hui Li, Jin; Myong, Lene; Skadegård, Mira C.; Yilmaz, Ferruh (Kvinder, Køn & Forskning, 2023)
Corrigendum to “Research and Education on Racism in Denmark - the state of the field and where to from here” published in Kvinder, Køn & Forskning 36(2), 21-28. The roundtable discussion was originally published on November 22, 2023, with the authors listed as Bontu Lucie Guschke, Iram Khawaja, and Lene Myong. The list of authors have been corrected on 08-12-2023 to acknowledge the collaborative efforts of the roundtable discussion, with the following names: Oda-Kange Midtvåge Diallo, Elizabeth Löwe Hunter, Jin Hui Li, Mira C. Skadegård, and Ferruh Yilmaz. The special issue editors apologize unreservedly for this omission. The roundtable discussion has been republished with the correct list of authors.